Flexible Aluminum-Air Battery Based on High-Performance Three-Dimensional Dual-Network PVA/KC/KOH Composite Gel Polymer Electrolyte - Zou, Chang (Langmuir : the ACS journal of surfaces and colloids, 2024)
With a large theoretical capacity and high energy density, aluminum-air batteries are a promising energy storage device. However, the rigid structure and liquid electrolyte of a traditional aluminum-air battery limit its application potential in the field of flexible electronics, and the irreversible corrosion of its anode greatly reduces the battery life. To solve the above problems, a PVA/KC/KOH (2 M) composite gel polymer electrolyte (GPE) with a three-dimensional dual-network structure consisting of polyvinyl alcohol (PVA), kappa-carrageenan (KC), and potassium hydroxide was prepared in this paper by a simple two-step method and applied in aluminum-air batteries. At room temperature, the ionic conductivity of the PVA/KC/KOH (2 M) composite GPE was found to be up to 6.50 × 10-3 S cm-1. By utilizing this composite GPE, a single flexible aluminum-air battery was assembled and achieved a maximum discharge voltage of 1.2 V at 5 mA cm-2, with discharge time exceeding 3 h. Moreover, the single flexible aluminum-air battery maintains good electrochemical performance under various deformation modes, and the output voltage of the battery remains at about 99% after 300 cycles. The construction of flexible aluminum-air batteries based on a three-dimensional dual-network PVA/KC/KOH composite GPE provides excellent safety and high-multiplication capabilities for aluminum-air batteries, making them potential candidates for various flexible device applications